2002
DOI: 10.1097/00007890-200203150-00012
|View full text |Cite
|
Sign up to set email alerts
|

Different effects of tacrolimus and cyclosporine on renal hemodynamics and blood pressure in healthy subjects

Abstract: We conclude that tacrolimus given during 2 weeks in the currently advised dosage has no unfavorable effects on renal hemodynamics and blood pressure in healthy individuals. The use of tacrolimus in organ transplant recipients may in the long-term lead to better renal function and less cardiovascular morbidity than the use of cyclosporine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
70
4
4

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 136 publications
(79 citation statements)
references
References 40 publications
2
70
4
4
Order By: Relevance
“…Differences in renal function between Larson's and other studies may be explained by the different anti-calcineurinic drugs used in the control group because it seems that CsA induces more profound renal hemodynamic changes than TAC, at least at the current target levels for clinical immunosuppression. 22 By exclusion of those with secondary immunosuppression, group A patients could obtain comparable renal function with group B patients after 5 yr, however, with high exclusion rate that exceeds 50%.…”
Section: Discussionmentioning
confidence: 90%
“…Differences in renal function between Larson's and other studies may be explained by the different anti-calcineurinic drugs used in the control group because it seems that CsA induces more profound renal hemodynamic changes than TAC, at least at the current target levels for clinical immunosuppression. 22 By exclusion of those with secondary immunosuppression, group A patients could obtain comparable renal function with group B patients after 5 yr, however, with high exclusion rate that exceeds 50%.…”
Section: Discussionmentioning
confidence: 90%
“…Although some have suggested that TAC is less nephrotoxic than CSA (4,20), these data are controversial and often based on short-term studies and on renal function (21). Most studies comparing TAC and CSA nephrotoxicity are in renal allografts where chronic rejection, hypertension, and recurrent disease may be confounding factors (3).…”
Section: Discussionmentioning
confidence: 99%
“…Animal studies have demonstrated that the vasoconstrictive effect of tacrolimus is weaker than of cyclosporine (205)(206)(207), and this was also confirmed in humans (208,209). Moreover, the fibrogenic potential of tacrolimus also appears to be lower (210), although these results could not be confirmed in a more recent study (135).…”
Section: Comparison Between Cyclosporine and Tacrolimusmentioning
confidence: 98%